Implementasi Sekolah Ramah Anak melalui Pengembangan Budaya Religius di SMAN 3 Kediri - Fitria Arifa Dewi (Peradaban Journal of Interdisciplinary Educational Research, 2023)
This research aims to examine the implementation of the Child-Friendly School (CFS) concept at SMAN 3 Kediri, constructed through a religious-cultural framework, to establish a safe and comfortable environment for students. A qualitative methodology was employed, with data collected through observations, documentation, and interviews involving both Islamic Studies teachers and students from various classes at SMAN 3 Kediri. The research findings reveal that SMAN 3 Kediri has integrated the principles of the CFS into the school’s culture, enriched by religious values. Implementation of the CFS concept at SMAN 3 Kediri, influenced by the religious-cultural approach, is manifested through a non-violent education approach, the elimination of discrimination, and an emphasis on enhancing children’s participation. The process of instilling a religious-cultural ethos within the educational context encompasses various methods, including role modeling, the application of reward and punishment systems (targhib and tarhib), habitual practices, and the dissemination of advice (mau’idzah).   Penelitian ini bertujuan untuk mengkaji implementasi konsep Sekolah Ramah Anak (SRA) di SMAN 3 Kediri, yang dibangun melalui budaya religius, dengan fokus pada pembentukan lingkungan yang aman dan nyaman bagi siswa. Metode kualitatif digunakan dengan data diperoleh melalui observasi, dokumentasi, dan wawancara yang melibatkan guru PAI dan siswa dari berbagai kelas di SMAN 3 Kediri. Hasil penelitian mengungkapkan bahwa SMAN 3 Kediri mengintegrasikan prinsip-prinsip SRA ke dalam budaya sekolah, yang diperkaya oleh nilai-nilai religius. Implementasi konsep SRA di SMAN 3 Kediri yang diperkaya oleh budaya religius diwujudkan melalui pendekatan pendidikan tanpa kekerasan, penghapusan diskriminasi, dan pemberian perhatian pada peningkatan partisipasi anak. Proses pembentukan budaya religius dalam konteks pendidikan melibatkan berbagai metode, termasuk keteladanan, penerapan sistem reward dan punishment (targhib dan tarhib), pembiasaan, serta penyampaian nasehat (mau’idzah)